2021
DOI: 10.3389/fnagi.2021.722580
|View full text |Cite
|
Sign up to set email alerts
|

Phosphodiesterase-4D Knockdown in the Prefrontal Cortex Alleviates Memory Deficits and Synaptic Failure in Mouse Model of Alzheimer’s Disease

Abstract: Phosphodiesterase 4 (PDE4)-dependent cAMP signaling plays a crucial role in cognitive impairment associated with Alzheimer’s disease (AD). However, whether inhibition of PDE4 subtypes or their splice variants in the prefrontal cortex positively regulates synaptic plasticity and antioxidative stress, and reverses β-amyloid 1–42 (Aβ1–42, Aβ42)-induced cognitive impairment still need to be clarified. The present study determined whether and how PDE4D knockdown by microinjection of lenti-PDE4D-miRNA into the prefr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…On the contrary, the PDE4D-sparing PDE4 inhibitor ABI-4 did not affect inflammatory processes in murine microglia cultures, excluding a direct role for PDE4D in inflammation (Hedde et al, 2017). Alternatively, PDE4D-specific inhibition has been largely related to improved memory and neuroplasticity (Mohammadnejad et al, 2021;Xiang et al, 2020;Zhang et al, 2017;Shi et al, 2021;Zhang et al, 2014;Sierksma et al, 2014;Cui et al, 2019). However, despite being a therapeutic target, it is hypothesized that especially PDE4D is responsible for the emetic side effects upon pan PDE4 inhibition since PDE4D is highly expressed in the area postrema, the chemoreceptor trigger zone for emesis in the brainstem, compared to other PDE4 genes (Mori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the PDE4D-sparing PDE4 inhibitor ABI-4 did not affect inflammatory processes in murine microglia cultures, excluding a direct role for PDE4D in inflammation (Hedde et al, 2017). Alternatively, PDE4D-specific inhibition has been largely related to improved memory and neuroplasticity (Mohammadnejad et al, 2021;Xiang et al, 2020;Zhang et al, 2017;Shi et al, 2021;Zhang et al, 2014;Sierksma et al, 2014;Cui et al, 2019). However, despite being a therapeutic target, it is hypothesized that especially PDE4D is responsible for the emetic side effects upon pan PDE4 inhibition since PDE4D is highly expressed in the area postrema, the chemoreceptor trigger zone for emesis in the brainstem, compared to other PDE4 genes (Mori et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several imprinted genes were related to behavioral functions. The second group, which involved the imprinted gene Ube3a , has been reported to regulate sleep homeostasis 57 ; the fifth group, which involved the imprinted gene Ntm , has been reported to be involved in motor function 58 ; the thirteenth group involved four imprinted genes ( Gpr1 , Nnat , Htra3 , and Pon2) , which regulate reproduction 59–62 ; and the fourteenth group involved four imprinted genes ( Dcd , 63 Ppo1r9a , 64 Slc22a2 , 65 and Pde4d 66 ) reported to mediate learning and memory.…”
Section: Discussionmentioning
confidence: 99%
“…Rolipram also prevents the decline of MMP and reduction of ATP levels in neurodegenrative diseases. [48][49][50][51][52] Previous studies have also shown that pentoxifylline inhibits the phosphodiesterase enzyme and enhances cellular cAMP and ATP, which may contribute to alleviate DN. [25,53] This effect seems to be related to the antiapoptotic effect of pentoxifylline.…”
Section: The Effects Of Rolipram And/or Pentoxifylline On the Number ...mentioning
confidence: 99%